Fat Liquefaction and Lipo Particles in a CIED Pocket During Generator Change-Not an Infection: A Rare Case Report - Guan A; He T; Huang X; Xia W; Shao Y (International Medical Case Reports Journal)
Aili Guan,1 Tao He,1 Xingang Huang,2 Wei Xia,1 Yibing Shao1 1Department of Cardiology, Heart Center, Qingdao Municipal Hospital, Qingdao, Shandong, 266071, People’s Republic of China; 2Department of Pathology, Qingdao Municipal Hospital, Qingdao, Shandong, 266071, People’s Republic of ChinaCorrespondence: Yibing Shao, Email syb2004@yeah.netAbstract: A case of fat liquefaction and fat particles in the pacemaker pocket observed in a female patient 12 years after implantation. The patient had no symptoms and no signs of infection or other discomfort of the heart and pacemaker pocket. The biochemical analysis showed a slight increase in cardiac troponin T, 0.026 ng/mL (reference range, < 0.016 ng/mL), a high increase in total cholesterol, 8.70 mmol/L (reference range, < 5.18 mmol/L), and low density lipoprotein, 5.38 mmol/L (reference range, < 3.37 mmol/L). Thick yellow liquid was seen to flow out of the pacemaker pocket when the pocket was opened, and many fat particles were found adhering to the wall of the pacemaker pocket during the pacemaker replacement procedure. Fat and fibrillar connective tissue with a few inflammatory cells, local tissue degeneration and necrosis were shown on immunohistochemical staining and no bacterial growth including anaerobic bacteria was observed. The aseptic necrosis of post-implantation complications is helpful for differential diagnosis in CIED complication. Moreover, the identification of fat liquefaction has important clinical significance for patient management and surgical decision-making.Keywords: fat liquefaction, fat particles, CIED pocket, CIED complications, CIED replacement